1-4lnx=lnx-9

Simple and best practice solution for 1-4lnx=lnx-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1-4lnx=lnx-9 equation:


Simplifying
1 + -4lnx = lnx + -9

Reorder the terms:
1 + -4lnx = -9 + lnx

Solving
1 + -4lnx = -9 + lnx

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-1lnx' to each side of the equation.
1 + -4lnx + -1lnx = -9 + lnx + -1lnx

Combine like terms: -4lnx + -1lnx = -5lnx
1 + -5lnx = -9 + lnx + -1lnx

Combine like terms: lnx + -1lnx = 0
1 + -5lnx = -9 + 0
1 + -5lnx = -9

Add '-1' to each side of the equation.
1 + -1 + -5lnx = -9 + -1

Combine like terms: 1 + -1 = 0
0 + -5lnx = -9 + -1
-5lnx = -9 + -1

Combine like terms: -9 + -1 = -10
-5lnx = -10

Divide each side by '-5nx'.
l = 2n-1x-1

Simplifying
l = 2n-1x-1

See similar equations:

| 10f+8=11f+7 | | 6(y+1)=2y+18 | | 4m+10=36 | | 23+5x=111-3x | | 7(51)=10 | | -2(3-7)-4= | | x=11+7y | | 2b+b=7 | | 13+3x=3n-29 | | 3y-2=4(2y-3) | | 13+3x=-29-3n | | 2.6=0.2-4 | | -2a+(5a-3)-(3a+4)= | | 8-3k+6k=2k-3 | | -4(x+3)-7=-3x-15 | | 6(w-3)-(2w-5)=3w | | y=-8/9x-8/9 | | -5+7x+7=8(x+3)-9 | | 12R=1/4M-5 | | 4x-28y=44 | | -2y+13=14-y | | g(p+2)=3x^2+3x+1 | | -2-k=-8 | | -4c+18=5c | | (1/3)9squarred | | 7x+8-5x=-2 | | 7b+3=5b-11 | | -6+6x+7=(x+1)-2 | | -40-8=6s | | -2=0-1/5j | | 9-5a+a=-3 | | 6n-7(n-1)=12 |

Equations solver categories